MEDICAL EDUCATION AND TRAINING FOR DISASTER MANAGEMENT: AN URGENT NEED: Medical Education - Hameed, Waqas; Hussain, M. Mazhar; Butt, Idrees Farooq; Aslam, Muhammad (Pakistan Armed Forces Medical Journal, 2006)
Disaster is a Greek word which means "bad star". It is a natural or man-made event that negatively affects life, property, livelihood or industry. It has often resulted in permanent changes to human societies, ecosystems and environment. Disasters manifest hazards that exacerbate vulnerable conditions for individuals and communities to threaten their survival and thrive.Most commonly occurring natural disasters include earthquakes, floods, windstorms, typhoons, drought, extremes of temperature and epidemic outbreaks. During past 20 years, natural disasters have claimed more than 3 million lives worldwide. These have affected at least 800 million people and resulted in damage to property exceeding US $50 billion [1].Pakistan is vulnerable to a number of natural hazards, of which floods, earthquakes, cyclones, windstorms, avalanches, drought and heat waves are the most significant. Floods, droughts and landslides in Pakistan tend to be frequent, seasonal, and localized. The snow melts at high mountains coinciding with the monsoon season and leads to very large discharges of the Indus River and its tributaries that results in annual floods. In February and March 2005, large areas of Pakistan were battered by rain, snowfall and flooding. The worst affected areas were NWFP, Northern Areas and Balochistan. Water supply, sanitation systems, electricity, communication and road links were severely affected. In Balochistan, nearly half a million people were affected, with more than 4,000 families left homeless. In NWFP more than 80,000 houses were destroyed and over 108,000 were damaged. A number of dams collapsed due to excessive flooding, causing severe destruction of crops and livestock [2].The earthquake hazard in Pakistan is high because of its vulnerable position on the eastern margin of the collision of the Indian plate with the Eurasian plate. These results in potential for major earthquakes in the north, where Indian plate thrusts under the Himalayas, and along the western edge of the country, where Indian plate transformation is relative to the Iranian and Afghan micro-plates and is expressed with the Chaman fault. The 1935 Quetta earthquake (60,000 killed) occurred on the Chaman fault. The Arabian plate subducts beneath the Iranian plate along Makran coast, where in 1945, earthquake of 7.9 magnitude resulted in a tsunami with 12 meter high waves. Karachi, east of the Makran coast, has significant seismic risk due to several nearby faults, including Allah Bund fault (1819 earthquake), and Pubb fault. The geological and seismic survey of Pakistan places the entire Sindh coastline (including Karachi) in a zone of “noticeable seismic danger” [2]. However the Oct. 8, 2005 earthquake has made it “mandatory” to update existing National Seismic Hazard Map of Pakistan.Pakistan is also exposed to extreme degree of hot weather during summer (May and June) which leads to melting of glaciers in North and extensive flooding of water in plains of Punjab and Sindh. This is followed by the monsoon season during July and August, that results in overflowing of rivers. Due to lack of adequate water reservoirs, there occurs extensive flooding of water in plains and mud slides in the North. Since 1935 the region where Pakistan is located has repeatedly experienced various natural disasters of which earthquakes and floods have been more dreadful. This has resulted in loss of life of thousands of people and affecting millions [3].